Strategi Manajemen Public Relations dalam Mempertahankan Loyalitas Pelanggan - Aziz Setiyawan; Husen Fahmi; Ani Yuningsih (Bandung Conference Series: Public Relations, 2022)
Abstract. In today, the creative wedding business is very strong, one of which is wedding organizer. The trend of organizing events also continues to grow. Organizing an event that is "current" and liked by millennials is one of them is marriage, this is inseparable from the help of a creative and professional wedding organizer. With limited resource conditions, using a wedding organizer is the right choice to keep the event memorable. Wedding organizer is a business that applies the concept of management continuously and consistently in exploring the world of entertainment as deeply as possible. For a wedding organizer, it is important for public relations management, both small-scale companies and large-scale companies. Through public relations management, two-way communication between organizations and the public (society) is reciprocal in order to support the functions and objectives of management by improving the development of cooperation and fulfillment of common interests. Including one of them for His Kologdam, is a company that provides services in the field of wedding organizers In this study researchers use qualitative methods using a case study approach that aims to find out how the public relations management strategy of His Kologdam in maintaining customer loyalty. From research that uses interview data collection techniques, observations, and documentation found the conclusion that his Public Relations management strategy is to conduct fact finding up to evaluation and create transactional communication to establish closeness with customers and make innovations and provide one stop service for customers. Abstrak. Di masa kini, bisnis pernikahan kreatif sangatlah kuat yaitu salah satunya Wedding organizer. Tren penyelenggaraan acara juga terus berkembang. Penyelenggaraan acara yang "kekinian" dan disukai para millennial salah satunya adalah pernikahan , ini tidak terlepas dari bantuan Wedding organizer yang kreatif dan profesional. Dengan kondisi sumber daya yang terbatas, menggunakan wedding organizer adalah pilihan tepat agar acara tetap berkesan. Wedding organizer adalah bisnis yang menerapkan konsep manajemen secara berkesinambungan dan konsisten dalam mengeksplorasi dunia entertainment sedalam-dalamnya. Bagi suatu wedding organizer penting adanya manajemen public relation, baik perusahaan yang berskala kecil maupun perusahaan berskala besar. Melalui manajemen public relation, komunikasi dua arah antara organisasi dengan publik (masyarakat) secara timbal balik dalam rangka mendukung fungsi dan tujuan manajemen dengan meningkatkan pembinaan kerja sama serta pemenuhan kepentingan bersama. Termasuk salah satunya bagi His Kologdam, merupakan suatu perusahaan yang menyediakan jasa di bidang wedding Organizer Dalam penelitian ini peneliti menggunakan metode kualitatif menggunakan pendekatan studi kasus yang bertujuan untuk mengetahu bagaiamana strategi manajamen Public relations dari His Kologdam dalam mepertahankan loyalitas pelanggan. Dari penelitian yang menggunakan teknik pengumpulan data wawancara, observasi, dan dokumentasi ditemukan kesimpulan bahwa strategi manajemen Public Relation His adalah dengan melakukan fact finding sampai dengan evaluation dan menciptakan komunikasi transaksional untuk menjalin kedekatan dengan pelanggan serta membuat inovasi dan memberikan layanan one stop service untuk pelanggan.